Diachronic Asymmetry as a Comparativist Problem - Cholakova, Zhorzheta (Zagadnienia Rodzajów Literackich, 2023)
This article offers an unpopular comparativistic method that does not fit into the previously known conceptual frameworks of comparative literature. In order to be more clearly distinguished from the hermeneutic practices existing in comparativistics, a brief overview of some basic views on the subject of comparative literature has been made. Thus, it becomes clear that we not only ignore the contactological aspect, but in order to apply this approach, it is necessary to prove the absence of any form of direct or indirect interaction. In terms of typology, we apply the requirement of non-appropriation to a common cultural area or direction. The manifestations of typological aspects (e.g., similar motives or characteristics of the character model) are seen as a consequence and not as a prerequisite for carrying out a comparativistic procedure. The proposed model is illustrated by paralleling two diachronously different artistic worlds for which there is factual evidence that they meet the criteria set by us — those of François Villon and Karel Hynek Mácha. We only consider the proposed comparativistic modus as possible without ignoring others. On the contrary, the tendency to extend the field of comparative literature offers us new options for rethinking dialogism not only as a direct explanation of interliterary relationships, but also as a system of returning questions about human existence at different times and in different national contexts.